The Relationship Between Qor-40 Questionary Value And Pupillary Pain Index As Assessment Of Recovery Quality On Post-Operating Patients Treated By Multimodal Analgesia (Parasetamol + NSAID + PCA OPIOID) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study analyzes the correlation between QoR-40 questionnaire value and the Pupillary Pain Indexas an assessment for the quality of recovery of postoperative patients receiving multimodal analgesia(Paracetamol + NSAID + PCA Opioid) in Dr. Soetomo Hospital. An observational analytic study withcross-sectional design was conducted on patients aged 18-60 years who underwent elective surgery withgeneral anesthesia at Dr. Soetomo Hospital Surabaya and receiving multimodal analgesia therapy, whichincludes intravenous paracetamol 4 x 500 mg, intravenous ketorolac 3 x 10 mg, and intravenous fentanyl viaPCA. Recovery quality checks were performed at 12 and 24 hours postoperatively. Retrieval of data in theform of a QoR-40 questionnaire and pupillary pain index examination using algiscan® pupillometry. Bothparameters will be analyzed by correlation test. The total need for fentanyl and PCA demand dose was alsoevaluated for use within 24 hours postoperatively. From 46 samples, obtained characteristics of studyarewidely distributed in terms of age, sex, anthropometry, and preoperative physical status. The average totalfentanyl PCA requirement is relatively small at 0.28 mcg / kg / hour. The correlation formed between QoR-40 and pupillary pain index is significant. It can be concluded that Pupillary Pain Index can replace the QoR-40questionnaire as an alternative assessment of the quality of recovery of patients after surgery